2017
DOI: 10.1097/aci.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Food labeling issues in patients with severe food allergies: solving a hamlet-like doubt

Abstract: So far, no laboratory technique is able to reassure the consumers about the composition of foods found on the packaging. International authorities produced increasingly stringent laws, but more is still to do.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Some foods are easily identifiable, others require extra attention. To safeguard the health of food allergic consumers, the health authorities of 66 countries over the five continents require by law that allergenic ingredients must be declared when used in prepackaged foods 13‐15 . Despite scrupulous observance of this prescription, accidental reactions to food may occur in greater proportion with the multiplicity of sensitizations.…”
Section: The Limits Of Food Avoidancementioning
confidence: 99%
“…Some foods are easily identifiable, others require extra attention. To safeguard the health of food allergic consumers, the health authorities of 66 countries over the five continents require by law that allergenic ingredients must be declared when used in prepackaged foods 13‐15 . Despite scrupulous observance of this prescription, accidental reactions to food may occur in greater proportion with the multiplicity of sensitizations.…”
Section: The Limits Of Food Avoidancementioning
confidence: 99%
“…18 On the other hand, a shared clinical threshold allowing the individuation of a legal limit on an allergen-by-allergen basis is not yet presently defined. 20 There are also few official analytical methods and limits of determination that are accepted as analytical reference in specific countries, such in the case of polymerase chain reaction (PCR) methods for allergen detection in Germany and Japan. 21 Overall, this poses a great risk for allergic people, as witnessed by the still observed reactions to food allergens, present even in countries with mandatory labeling.…”
Section: International Requirements For Allergenic Ingredients Labellingmentioning
confidence: 99%
“…Public health interventions, such as public health measures to address food labeling and packaging controls, would also be beneficial. 63 Perceived contamination creates stress when eating in restaurants or food service establishments, because a significant number of food reactions occur when eating food from these settings, even when staff are informed of the food allergy in advance. 64 Results from a survey of restaurants indicated that managers and staff were generally knowledgeable about food allergies and willing to accommodate customers' food allergies, but misconceptions were still reported, such as belief that a person with food allergy can safely consume a small amount of the allergen.…”
Section: Public Health Interventionsmentioning
confidence: 99%